Improving fitness professionals' awareness and understanding of eating disorder symptoms: Effects of a brief interventionPractical implications: - Stephanie Boulet; Alexander Blaszczynski; Jane Miskovic-Wheatley; Dylan Pickering; Sarah Maguire (Elsevier, 2023)
Summary: Objectives: Eating disorders (EDs) are complex, potentially life-threatening mental illnesses associated with low detection in health settings and low treatment rates. Compulsive exercise is a common ED feature, with symptoms likely to manifest in fitness settings. Fitness professionals are ideally placed to identify ED indicators among clients, to encourage help-seeking, and to offer referrals to specialist treatment services. This study aimed to investigate whether existing industry guidelines in Australia (i.e., "Eating Disorders: Recommendations for the Fitness Industry") help to improve fitness professionals' awareness and understanding of ED symptoms and appropriate interventions when detected among clients. Design: Cross sectional study; randomised controlled trial Methods: 174 fitness professionals practicing in Australia completed an anonymous online survey. Participants were presented with two vignettes of fictional clients displaying ED indicators and were assessed on their ability to identify ED symptoms and consider appropriate responses. A subgroup of randomised participants was exposed to industry ED recommendations prior to the second vignette, to assess the impact of guideline exposure. Results: Most participants (87.36%) were unaware/unfamiliar with the recommendations at baseline. After exposure to the recommendations, participants in the treatment condition showed small improvements in their ability to identify ED symptoms and their self-reported likelihood of intervening, compared to control participants who were not exposed. Conclusions: More widespread exposure to existing ED recommendations may be a worthwhile step to enhance the awareness and knowledge of fitness professionals interacting with clients with EDs. This study further highlights the need for more in-depth and empirically tested educational resources and programs to optimise early detection and intervention of EDs in fitness settings.